Put this in easy words:To find the zeros of the quadratic function y = 6x² + 13x + 5, we can use the quadratic formula, which is written as x = (-b ± √(b² - 4ac)) / (2a). In this equation, a, b, and c are the numbers from our quadratic equation, where a = 6, b = 13, and c = 5. First, we need to calculate something called the discriminant, which is found using the formula b² - 4ac. For our equation, we calculate b², which is 13² = 169, and 4ac, which equals 4 × 6 × 5 = 120. Now, we subtract 120 from 169 to get the discriminant: 169 - 120 = 49.Next, we can plug our values into the quadratic formula. This gives us x = (-13 ± √49) / 12. Since the square root of 49 is 7, we can rewrite the formula as x = (-13 ± 7) / 12. This leads us to two possible values for x: for the first solution, we calculate x₁ = (-13 + 7) / 12 = -1/2. For the second solution, we find x₂ = (-13 - 7) / 12 = -20/12 = -5/3. Therefore, the zeros of the quadratic function y = 6x² + 13x + 5 are x = -1/2 and x = -5/3. To find the zeros of the quadratic function y = 6x² + 13x + 5, we can use the quadratic formula, which is written as x = (-b ± √(b² - 4ac)) / (2a). In this equation, a, b, and c are the numbers from our quadratic equation, where a = 6, b = 13, and c = 5. First, we need to calculate something called the discriminant, which is found using the formula b² - 4ac. For our equation, we calculate b², which is 13² = 169, and 4ac, which equals 4 × 6 × 5 = 120. Now, we subtract 120 from 169 to get the discriminant: 169 - 120 = 49.Next, we can plug our values into the quadratic formula. This gives us x = (-13 ± √49) / 12. Since the square root of 49 is 7, we can rewrite the formula as x = (-13 ± 7) / 12. This leads us to two possible values for x: for the first solution, we calculate x₁ = (-13 + 7) / 12 = -1/2. For the second solution, we find x₂ = (-13 - 7) / 12 = -20/12 = -5/3. Therefore, the zeros of the quadratic function y = 6x² + 13x + 5 are x = -1/2 and x = -5/3.

3 answers

To find where the quadratic equation \( y = 6x^2 + 13x + 5 \) equals zero, we use a formula called the quadratic formula. This formula looks like this:

\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]

In our equation, \( a = 6 \), \( b = 13 \), and \( c = 5 \).

First, we calculate something called the discriminant, which helps us understand the solutions. We use the formula:

\[ b^2 - 4ac \]

So, we calculate:

  • \( b^2 = 13^2 = 169 \)
  • \( 4ac = 4 \times 6 \times 5 = 120 \)

Next, we subtract \( 120 \) from \( 169 \) to find the discriminant:

\[ 169 - 120 = 49 \]

Now, we can use the quadratic formula. We plug in our values:

\[ x = \frac{-13 \pm \sqrt{49}}{12} \]

Since the square root of \( 49 \) is \( 7 \), we can simplify it to:

\[ x = \frac{-13 \pm 7}{12} \]

This gives us two possible answers for \( x \):

  1. For the first solution, we calculate:

\[ x_1 = \frac{-13 + 7}{12} = \frac{-6}{12} = -\frac{1}{2} \]

  1. For the second solution, we find:

\[ x_2 = \frac{-13 - 7}{12} = \frac{-20}{12} = -\frac{5}{3} \]

So, the solutions (or "zeros") of the equation \( y = 6x^2 + 13x + 5 \) are:

\[ x = -\frac{1}{2} \quad \text{and} \quad x = -\frac{5}{3} \]

Put this in a paragraph and make it keyboard font

Sure! Here is the information in a single paragraph using keyboard font:

To find where the quadratic equation y = 6x^2 + 13x + 5 equals zero, we use the quadratic formula: x = (-b ± √(b² - 4ac)) / (2a). In this equation, a = 6, b = 13, and c = 5. First, we calculate the discriminant using b² - 4ac. We find b² = 13² = 169 and 4ac = 4 × 6 × 5 = 120. Subtracting 120 from 169 gives us the discriminant: 169 - 120 = 49. Plugging our values into the quadratic formula, we have x = (-13 ± √49) / 12. Since the square root of 49 is 7, we rewrite it as x = (-13 ± 7) / 12. This leads to two possible values for x: x₁ = (-13 + 7) / 12 = -1/2 and x₂ = (-13 - 7) / 12 = -20/12 = -5/3. Therefore, the solutions (or "zeros") of the equation y = 6x² + 13x + 5 are x = -1/2 and x = -5/3.